Greening the Wind : Environmental and Social Considerations for Wind Power Development - Ledec, George C.; Rapp, Kennan W.; Aiello, Roberto G. (World Bank, 2012)
This report identifies good practices for managing the key environmental and social issues associated with wind power development and provides advice on how best to address these issues in project planning, construction, and operation and maintenance. It provides detailed background information on wind power, with special focus on two emerging themes of growing scientific and public interest: namely the biodiversity-related impacts and the broader socioeconomic and cultural dimensions of wind power development. Like wind power itself, the scope of this report is worldwide although special attention is paid to the issues characteristic of the Latin America and Caribbean (LAC) region. While the principal focus is on land-based wind power, it also briefly addresses the environmental and social impacts related to off shore wind development. Wind power today is widely regarded as a key component of an environmentally sustainable, low-carbon energy future because it is renewable, requires almost no water, and generates near-zero emissions of greenhouse gases and other pollutants. In many parts of the world, wind power has the potential to significantly reduce greenhouse gas (GHG) emissions from electric power generation, thereby helping to limit the severe environmental and social consequences of human-induced climate change. The growth of wind power has also occurred due to its other positive attributes, including growing economic competitiveness. The adverse biodiversity-related impacts of wind power facilities mainly involve birds, bats, and natural habitats.